Trends in income distribution in the post- World War II period: Evidence and interpretation - Giovanni Andrea Cornia; Sampsa Kiiski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Until recently, the literature on income inequality within countries suggested that trends in this area had remained stable over the last few decades, and that there is no relation between changes in inequality on the one side and domestic and external liberalization on the other. Against this background, our study reviews changes in within-country inequality over the last twenty years on the basis of an extensive review of the literature and of an analysis of inequality trends in 73 countries accounting for over four-fifths of world population and GDP. The paper finds that over the last two decades inequality rose in twothirds of these 73 countries. This pattern is not uniform but marks a clear departure from the inequality trends recorded since the end of World War II. The paper also suggests that, with the exception of growing educational dispersion in Latin America, traditional causes of inequality (such as land concentration and urban bias) cannot explain the recent rise in income inequality. The latter appears to be related to a shift towards skill-intensive technologies and, especially, to the drive towards domestic deregulation and external liberalization.
Keywords: E62; H53; I38; 330; policy reform; Washington Consensus; inequality; inequality trends; liberalization; Einkommensverteilung; Welt